Nilai-nilai Pendidikan Karakter Integritas dalam Novel Buya Hamka - Aini, Rasidah; Fatria, Fita (Melati Institute, 2024)
Character education is an important part of the educational process which aims to form individuals with good personalities and high morality. The importance of character education increases in the modern era, where moral and ethical challenges are increasingly complex. Literature, as a form of art and human expression, is very good at conveying the principles of character education. This study can also contribute to understanding how literature can be an effective means of conveying moral messages to readers. This research uses a descriptive qualitative research approach. This approach focuses on the meaning, experience, and context surrounding the phenomenon under study. The data source in this research is the novel